'It's the little things that count'. Families' experience of roles, relationships and quality of care in rural nursing homes. (10th May 2014) - Ryan, Assumpta Ann; McKenna, Hugh
<x xml:space="preserve">Abstract</x> Background Entry to long‐term care is an emotional time for older people and their families. Poor communication and uncertainty about roles and responsibilities in the post‐placement period can cause distress for families and staff, further exacerbating an already difficult situation. However, there are limited studies that specifically address roles and relationships between families and care home staff in the post‐placement period. Aim The aim of this study was to explore the experiences of families following the nursing home placement of an older relative. Design A qualitative approach using grounded theory methodology was used to conduct the study. Method Semi structured interviews were conducted with 29 relatives of nursing home residents in a region of the UK. Consistent with grounded theory methodology, data collection and analysis occurred simultaneously. Findings Data analysis revealed five distinct categories that captured the experience of families in the post‐placement period. These were: communication with staff, involvement in relative's care, the importance of 'the little things', quality of care and areas for improvement. Conclusions Developing caring partnership is crucial if the resources of care home staff and families are to be maximised for the benefit of all concerned. Implications for practice A number of programmes and initiatives already exist to enhance the quality of life of older people in care homes and their families. Serious consideration should be given to more widespread uptake of these initiatives.